(untitled) (Journal of the Bangladesh Agricultural University, 2020)
This study was conducted to evaluate the influence of partial replacement of concentrate mixture (CM) by hydroponic maize fodder (HMF) on the performance of crossbred cow. Six Holstein-Friesian crossbred (HFX) lactating cows were selected and divided into two groups, control (n = 3) and hydroponic (n = 3). Both the control and hydroponic cows received 37.0 kg/head/day German grass (Echinochloa crus-galli). In control group, 4.0 kg CM was supplied daily to each cow and 25% of CM was replaced by HMF (6.1 kg/h/d) in the hydroponic group. The dry matter intake and body weight between control and hydroponic groups were found similar (P > 0.05). During the study period, about 21% higher (P < 0.001) milk was obtained in the hydroponic group compared to the control group. Compared to initial day of the study, average of 28 days milk yield was found 11% more in hydroponic group, whereas, milk production of control group was declined. Feed conversion efficiency was found higher (P < 0.001) in hydroponic group than that of the control group (1.25 vs. 1.63 kg DMI/kg milk yield and 0.76 vs. 0.97 kg TDNI/kg milk yield). Total solids (P < 0.001), fat (P = 0.004) and ash (P = 0.008) contents of milk were found higher in hydroponic group compared to the control group but other milk compositional parameters remains similar between two dietary groups. In conclusion, feeding of hydroponic maize fodder to HFX cows has positive impacts in boosting up the milk production, feed efficiency and milk composition. J Bangladesh Agril Univ 18(3): 629–635, 2020 https://doi.org/10.5455/JBAU.98462